Information Science as object: Epistemologies as meeting spaces - Rabello, Rodrigo [UNESP] (FapUNIFESP (SciELO), 2012)
Information Science (IS) counts on a singular investigative place where interdisciplinarity operates as a device to study phenomena related with its fuzzy object: information. It is one of the causes originating an identity crisis reflected in the demarches of validation, along with this productive setting, in epistemic terms of its disciplinarity. In order to introduce spaces where such theoretical efforts are produced, this paper aims to: a) introduce perspectives of analyses, or places of observation, where narratives within the field of IS are produced; b) bring a theoretical framework containing explanations and/or controversies illustrating a search for the disciplinary construction of IS. For such, three epistemologies were used as analysis categories: i) specific; ii) particular; and iii) global. These categories, taken from Hilton Japiassu, helped identifying the position of the subject, i.e. the philosopher, as for the study object - in this case, IS. The narratives produced within the field have been directed in well defined epistemological spaces, although, at times, they seem to follow a transversal trajectory in intermediate sites, providing productive epistemological meeting spaces.
A Ciência da Informação como objeto: Epistemologias como lugares de encontro
Keywords: Epistemology; Information Science; Production of narratives